Fabric and the critical state of idealized granular assemblages subject to biaxial shear - Yan, W.M.; Zhang, Lin (Computers and geotechnics, 2013)
A series of numerical biaxial tests using the discrete element method are performed to study the effect of initial fabric on the mechanical responses of granular materials subject to biaxial shear. Idealized granular specimens comprised of mono-sized, two-dimensional, elongated particles are carefully prepared so that the specimens have identical densities, but systematically-distinctly different initial fabrics before shear. The macroscopic stress–strain response and microscopic directional statistical information including the geometrical arrangement of the particles, contact forces, and void space distribution are monitored during the test. The directional distribution is described by the two scalar qualities: one characterizes the degree of anisotropy while the other describes the preferential orientation with respect to the major principal stress plane. While the evolution of the assemblages’ macroscopic and microscopic responses is explored, the ultimate aim of this study is to shed light on the existence and uniqueness of the critical state for granular materials. The results show an anisotropic distribution of particle arrangement, contact force and void space upon shear. At very large strain, particles are aligned with their long axis parallel to the major principal stress plane. Normal contact force is parallel to the loading direction. Void space shows a preferential direction along the major principal stress direction. More importantly, a unique stress–density–fabric relation is observed at the critical state when the shear strain becomes significantly large.